The Nobel Laureates' campaign supporting GMOs - Richard J. Roberts (Journal of Innovation & Knowledge (JIK), 2018)
More than 800 million people suffer from hunger in the world. Using modern plant breeding methods to generate so-called GMOs (Genetically Modified Organisms), agricultural scientists have shown that crop yields and nutritional quality can be greatly improved. Many GMO varieties have been specifically developed with the aim of being resistant to pests, tolerant to drought and containing beneficial nutrients. This leads to a reduction in the use of insecticides in water and on land. If anything, the GMO varieties are safer than traditionally bred varieties because they are made in a very precise manner. However, the scientific evidence on this issue is being ignored by the Green Parties such as Greenpeace who continue to deny the science and mislead the public. 129 Nobel Laureates have joined in a campaign to convince the Green Parties and the public that they should support the use of GMOs, especially for the sake of the developing world.
Keywords: 650; GMO; Hunger; Nutrition; Crop; Pest; Food; Precision agriculture